Evoluç\~ao dos investimentos nas três frentes de expans\~ao da economia Brasileira na década de 2000 - Ricardo Bielschowsky; Gabriel Coelho Squeff; Lucas Ferraz Vasconcelos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– In this paper we examine from a sectoral point of view the main trends of investment in the Brazilian economy in the 2000s and its relation to value added and to imports and exports coefficients. It is argued for the existence of three expansion fronts: infrastructure, natural resources and mass consumption. Reinforcing that classification, investments in these three fronts grew 10% per annum between 2004 and 2008. Despite the evidence that these investments were concentrated in the modernization, it is concluded that the three expansion fronts allow a new wave of investment focused on expansion, diversification and innovation.
Keywords: E22; E23; O11; 330; investment; value added; economic development